Imported Intermediate Goods and Incomplete Exchange Rate Pass-Through into Export Prices - Alexander Firanchuk (ZBW – Leibniz Information Centre for Economics, 2018)
This paper analyses the effect of imported inputs and the exporting country share on the degree of exchange rate pass-through (ERPT) into export prices. I present a model where firms set variable markups under oligopoly competition and imported inputs affect marginal cost. It makes two predictions: (i) the imported input share reduces ERPT (ii) the exporting country share in a destination market increases ERPT. Using industry-level data, I test the hypotheses for 57 countries over the period 2000-2015. For trade between advanced economies, imported inputs reduce ERPT, but only in the case of producer currency movements. Controlling for exporting country share, the pass-through elasticity is 39% when imported inputs are not used, but 11% when the share of imported inputs in gross exports rises to one half.
Keywords: F12; F14; F31; F41; 330; exchange rate pass-through; export prices; global value chains